Do pai ao pa(i)terno: vicissitudes da constituição da paternalidade - Angelelli, Arianne Monteiro Melo (2022)
This research is about father’s withdrawal from perinatal scene in consequence of psychic illness. Parenting role is a subjective reorganization process that depends on cultural, social, and psychic features that can lead to a significant life crisis. The baby’s arrival evokes triangular conflicts and archaic anxieties arising from parents’ early development stages. Fathers and mothers tend to experience the perinatal transition in distinct ways. This research focuses on the favorable and unfavorable circumstances that benefit or hinder the constitution of the first tender and love bonds between father and child. The baby’s maturational process is facilitated by a fathering presence and the contribution of a supporting environment, although fatherhood does not need to be performed by the biological father. Short case histories are drawn from the author’s clinical psychiatric and psychoanalytic practice and from John Updike’s novel Rabbit, Run on father’s illnesses, difficulties, and the abandoning of a pregnant wife with tragic consequences. The clinical cases and Updike’s story lead to reflections on men’s anxieties and defensive mechanisms during perinatal crisis. Theories by Melanie Klein and Winnicott are used to raise the hypothesis that intense manic defenses are frequently used to react against helplessness situations and primary feminine identifications that are evoked at perinatal situation